2022
DOI: 10.1016/j.xops.2021.100089
|View full text |Cite
|
Sign up to set email alerts
|

Gain of Chromosome 6p Correlates with Severe Anaplasia, Cellular Hyperchromasia, and Extraocular Spread of Retinoblastoma

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…For instance, Josefina et al documented a 6p gain in 14 out of 16 extraocular RB samples, compared to none in 17 intraocular RB samples using comparative genomic hybridization 29 . Gustav et al found a 6p gain in 5 out of 6 extraocular RB samples against 13 out of 36 intraocular RB samples through whole genome sequencing 30 . Both findings underscore the potential link between 6p gain and the local extension of RB.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Josefina et al documented a 6p gain in 14 out of 16 extraocular RB samples, compared to none in 17 intraocular RB samples using comparative genomic hybridization 29 . Gustav et al found a 6p gain in 5 out of 6 extraocular RB samples against 13 out of 36 intraocular RB samples through whole genome sequencing 30 . Both findings underscore the potential link between 6p gain and the local extension of RB.…”
Section: Discussionmentioning
confidence: 99%
“… 44 Interestingly, 6p gain also associated with high-risk histopathologic features in enucleated eyes. 45 …”
Section: Can Ah Sampling Aid In Prognosis Of Rb?mentioning
confidence: 99%
“…67,68 Gain of chromosome 6p is associated with the risk of intraocular relapse 69 and extraocular disease. 70 Circulating blood RB1-mutant DNA may be associated with extraocular disease. 71 Aberrant methylation portends aggressive tumor behavior.…”
Section: Retinoblastomamentioning
confidence: 99%
“…Recent advances in aqueous humor liquid biopsy (Figure 1) have facilitated the detection of molecular biomarkers in vivo, and there is a growing understanding of their prognostic implications and inter‐eye heterogeneity 67,68 . Gain of chromosome 6p is associated with the risk of intraocular relapse 69 and extraocular disease 70 . Circulating blood RB1‐ mutant DNA may be associated with extraocular disease 71 .…”
Section: Introductionmentioning
confidence: 99%